2006
DOI: 10.1103/physrevlett.96.117204
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Exchange Bias with Diluted Antiferromagnets

Abstract: The exchange bias H(E) of coupled polycrystalline films of antiferromagnetic CoO and ferromagnetic Co was significantly enhanced by the systematic substitution of nonmagnetic Mg for Co in CoO. Samples in which either Co or Co(1-x)Mg(x)O were deposited first were investigated at temperatures from 10 to 300 K. With Co(1-x)Mg(x)O on the bottom, the increased interfacial uncompensated spin density of the single antiferromagnetic domain Co(1x)Mg(x)O crystallites produced the enhanced H(E). With Co on the bottom, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 12 publications
7
54
2
Order By: Relevance
“…5). This result shows that the rotatable and frozen spins distribute uniformly inside the entire CoO film, supporting the doping and FM/AFM/FM results [25][26][27][28][29] that the exchange bias depends on the bulk AFM spin structure. It should be mentioned that the NiO spins are much softer than CoO spins due to a much weaker NiO magnetic anisotropy [37].…”
supporting
confidence: 74%
See 1 more Smart Citation
“…5). This result shows that the rotatable and frozen spins distribute uniformly inside the entire CoO film, supporting the doping and FM/AFM/FM results [25][26][27][28][29] that the exchange bias depends on the bulk AFM spin structure. It should be mentioned that the NiO spins are much softer than CoO spins due to a much weaker NiO magnetic anisotropy [37].…”
supporting
confidence: 74%
“…The result shows clearly a correlation between the FM and the AFM domains, and the existence of a small amount of uncompensated spins in the AFM layer [19]. It was further shown that only a small percentage of the uncompensated spins is pinned to account for the exchange bias [20,21,22,23] and that these pinned uncompensated AFM spins actually extend into the AFM layer [24], suggesting a bulk-like effect of the AFM spins in the exchange bias [25,26,27,28,29]. Despite the above progress, the compensated AFM spin behavior remains unclear during the FM layer reversal.…”
mentioning
confidence: 91%
“…This magnetic 'hardening' originates from the OSEC overlayer, and is consistent with the enhanced exchange interaction found previously for π-conjugated molecules deposited on FM surfaces due to the proximity of the molecules to the FM atoms [42]. [43,44], which results from an AFM coupling [23] at the interface between the Feq3 and NiFe layers. We note that π-conjugated nonmagnetic organic molecules deposited on FM metallic film show only a symmetric M(B) response [4,12,42].…”
Section: B Magnetization Measurementssupporting
confidence: 89%
“…11,12 Factors of 2 or greater enhancements of H E for dilute FM/AF Co x Mg 1−x O / Co bilayers were found for x ϳ 0.80 ͑compared to x =1͒, [11][12][13] and more recently enhancements of H E in polycrystalline Co x Mg 1−x O / Co bilayers have been observed. 14 In Co/twinned Zn 0.17 Fe 0.83 F 2 bilayers, a 65% increase in H E with respect to pure Co/twinned FeF 2 bilayers was observed. 15 However, in Co/untwinned single crystalline Fe x Zn 1−x F 2 bilayers, no significant enhancement of H E was observed, presumably due to a lack of percolation of nonmagnetic impurities at higher Fe concentrations.…”
Section: Introductionmentioning
confidence: 87%